Analisis Faktor Yang Berhubungan Dengan Postur Kerja Karyawan di Kantor Pusat PT Jasa Marga (Persero) Tbk - Nur Asniati Djaali; Dhea Sylvia Fajriah (Jurnal Ilmiah Kesehatan, 2020)
Work posture is the position of the body when doing work activities. Incorrect work posture is often caused by the location of equipment or facilities, workplace layout, inappropriate work environment conditions, or a combination of several of these factors. Any body position can cause discomfort and fatigue if maintained for a long time, including workers in the office. Therefore this study will be carried out Observation ns of workers at the Head Office of PT. Jasa Marga who works for 8 hours per day using a computer. To minimize the level of injury risk by knowing and identifying work postures on workers using computers. To assess the ergonomic risk of office workers that can cause Musculoskeletal Disorder is by observing ROSA. This research is a quantitative study with a cross-sectional study design. The statistical test used is Chi-square. And using simple random Sampling as many as 88 people. Univariate test results of this study showed that as many as 50 people have a high-risk work posture. based on the results of the bivariate test, it was found that the variables associated with work posture using the ROSA method were anthropometri factors and sports activity factors with p value 0.006 and 0.042. To prevent or reduce high-risk work posture should do modify or replace workstation in the office, and perform workplace stretching exercise when the muscles begin to tense.